Medical Students’ Preparedness for Apprenticeship Learning - Jodi Jarecke; Maryellen Gusic; Edward W. Taylor (Adult Education Research Conference, 2008)
This research investigated medical student and clinical faculty perceptions of preparedness for learning in the clinical setting. It also explored their beliefs about the ways in which the curriculum promotes or fails to promote preparedness for apprenticeship learning.
Keywords: medical education; situated cognition; communities of practice